2007
DOI: 10.1111/j.1479-8425.2006.00248.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between sleep knowledge, sleep practice and sleep quality

Abstract: To help alleviate the widespread health problem created by poor sleep, health organizations invest considerable resources into public sleep education. Yet there is limited research to support the notion that sleep education leads to better sleep quality, whether for poor sleepers or the general population. The present study examined the relationships between sleep knowledge, sleep practice and sleep quality in a sample of 946 participants (mean age = 38.5 years, SD = 14.4, 67% women), 394 of whom were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 22 publications
4
33
0
Order By: Relevance
“…The improvements in sleep hygiene and sleep quality reported in the current study are also consistent with previous studies that have shown similar findings in participants ranging from infants to adults [21,24,40-42]. However given both participants and parents were aware of the treatment, a study of sleep hygiene intervention with a concurrent control group with parents blind to treatment would be required to provide definitive answers in regard to efficacy.…”
Section: Discussionsupporting
confidence: 89%
“…The improvements in sleep hygiene and sleep quality reported in the current study are also consistent with previous studies that have shown similar findings in participants ranging from infants to adults [21,24,40-42]. However given both participants and parents were aware of the treatment, a study of sleep hygiene intervention with a concurrent control group with parents blind to treatment would be required to provide definitive answers in regard to efficacy.…”
Section: Discussionsupporting
confidence: 89%
“…We found that sleep hygiene knowledge had no relationship with behavioural intention, and was not correlated with sleep hygiene behaviour and sleep quality in the whole sample. We cautioned that the measurement we used to assess sleep hygiene knowledge had limited psychometric property, an alpha of 0.65, when first developed (Gallasch and Gradisar, ). Further, in our analysis of running the original model separately in adolescents who had poor sleep hygiene knowledge and those had good sleep hygiene knowledge, we demonstrated that an interaction effect of sleep hygiene knowledge exists in our model.…”
Section: Discussionmentioning
confidence: 99%
“…Sample items include: ‘Drinking three standard glasses of alcohol has no effect on sleep’ and ‘If you cannot fall asleep within 20 min, you should get out of bed and try again later’. The internal consistency of the sleep knowledge questionnaire is somewhat acceptable ( α = 0.65) (Gallasch and Gradisar, ).…”
Section: Methodsmentioning
confidence: 99%
“…Sleep quality is positively correlated with global measures of sleep-promoting practices, even though the link between sleep knowledge and sleep quality has not been substantiated (Gallasch & Gradisar, 2007;Suen et al, 2008). Moreover, factors that influence the translation of sleep knowledge into sleep practices have not been addressed in the literature.…”
Section: Introductionmentioning
confidence: 96%